Wacana Sinkronis Digital sebagai Inovasi Media Pembelajaran Analisis Wacana pada Mahasiswa TBIN UIN Madura - Zainuri Ihsan; Mochamad Arifin Alatas; Aldi Firnanda (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study discusses the use of Digital Synchronous Discourse as an innovation in learning media, especially in the context of discourse analysis by students of the Indonesian Language Education Study Program (TBIN) at IAIN Madura. This innovation emerged as a response to the need for a more interactive learning method, relevant to technological developments, and able to encourage active student involvement. The purpose of this study was to examine the effectiveness and implementation of digital synchronous discourse in discourse analysis learning and to determine its impact on students' understanding and analytical skills. The method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation of classroom learning activities. The results of the study showed that the use of digital media synchronously was able to increase student participation, enrich the sources of discourse analyzed, and provide a wider space for reflection in understanding the context and structure of discourse. In conclusion, Digital Synchronous Discourse is an effective and innovative approach in supporting discourse analysis learning, especially in the digital era that demands flexibility and interactivity in the teaching and learning process.